APPLICATION OF ACOUSTIC MATERIAL FOR FACADE TO REDUCE NOISE IMPACT IN BUILDING LOCATED NEAR FROM RAIL - Ayu Panji Wilda Kusuma; Sri Nastiti N. Ekasiwi; Dhany Arifianto (Journal of Architecture&ENVIRONMENT, 2015)
Facade is a main component to reduce noise impact from the outdoor area. A room is considered as a cozy place, if the condition is set with Noise Criteria (NC) of 30-35 dB (A). The standards of room comfort should be applied in each area, one of them is Hotel Sahid Surabaya building located close to the railway. Acoustic insulation is certainly necessary and applied in some elements of the facade building. A way to improve the comfort in the building is with selection of materials that will be applied to the interior wall. In addition there is reference such as the use of diffuser on the exterior wall. This research is about the increasing of acoustic insulation on the hotel room facade with case study of Sahid Hotel Surabaya by measuring level of acoustic insulation on the inner wall and outer wall in one of the hotel room. The research study is focused on the noise impacts caused by airborne sound. This research use quasi experiment. The research objectives of this paper are to inform the wall insulation material in buildings and as a reference of the use exterior wall diffuser which are suitable for outdoor area. According to the earlier research, the use of a diffuser on the exterior facade is able to reduce noise until 30-35%. As for the results of an alternative design, the use of insulation material in the form of fibers with fiber type-800 on the inner wall has produced good insulation levels. This study is expected as a reference for designing especially buildings located close to the rail to support the acoustic comfort.